Identification of candidate network hubs involved in metabolic adjustments of rice under drought stress by integrating transcriptome data and genome-scale metabolic network. (January 2016) - Mohanty, Bijayalaxmi; Kitazumi, Ai; Cheung, C.Y. Maurice; Lakshmanan, Meiyappan; de los Reyes, Benildo G.; Jang, In-Cheol; Lee, Dong-Yup
Graphical abstract: Highlights: Developed and demonstrated a novel approach to identify targets for plant breeding. Integrated rice drought stress transcriptome with genome-scale metabolic network. Identified cis -elements among co-expressed drought responsive metabolic genes. Associated the cis -elements with differentially expressed transcription factors. Identified AP2/ERF, bZIP, MYB and NAC linked to known drought-associated QTLs. Abstract: In this study, we have integrated a rice genome-scale metabolic network and the transcriptome of a drought-tolerant rice line, DK151, to identify the major transcriptional regulators involved in metabolic adjustments necessary for adaptation to drought. This was achieved by examining the differential expressions of transcription factors and metabolic genes in leaf, root and young panicle of rice plants subjected to drought stress during tillering, booting and panicle elongation stages. Critical transcription factors such as AP2/ERF, bZIP, MYB and NAC that control the important nodes in the gene regulatory pathway were identified through correlative analysis of the patterns of spatio-temporal expression and cis -element enrichment. We showed that many of the candidate transcription factors involved in metabolic adjustments were previously linked to phenotypic variation for drought tolerance. This approach represents the first attempt to integrate models of transcriptional regulation and metabolic pathways for the identification of candidate regulatory genes for targeted selection in rice breeding.